(untitled) (Comparative & International Education Series, 2022)
Resilience can be observed as a fundamental and multifaceted component that allows global higher education students to be better prepared to manage challenges. Those experiences would give them a remarkable ability to cope with problems they might face in their future workplaces, positioning them as leaders. This study aims to describe the graduate student’s experience of developing their leadership resilience during the pandemic. This paper sheds light on building leadership resilience for international graduate students. This study used a self-reflection approach. Three critical tenets, a sense of belonging, community creation, and self-efficacy, were selected to explore literature reviews and utilize them as prompts to illustrate and share experiences regarding leadership resilience during the pandemic.